Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have 3 expressions:

$f(x)=e^{ikx}+Ae^{-ikx}; g(x)= Be^{kx}+Ce^{-kx}; h(x)=De^{ikx}$

I want to find $|A|^2$ by letting

${f'(0)\over f(0)}={g'(0)\over g(0)}$ and ${g'(a)\over g(a)}={h'(a)\over h(a)}$

I have done the calculations myself and got $|A|^2=1$. But this is not the expected answer. Could someone tell me if I have made a mistake?


share|cite|improve this question
How does letting those things equal each other help you find anything? It looks to me like $A=f(0)-1$ is a pretty swift route and the other two functions are irrelevant. Is there more to this question than what you've written here? – anon Oct 22 '11 at 9:40
I am getting A=0. what is the expected answer?? – Ramana Venkata Oct 22 '11 at 9:45
@craig: you probably should be posting your actual problem. – J. M. Oct 22 '11 at 9:49
@craig Can you tell the entire question?? – Ramana Venkata Oct 22 '11 at 9:49
@RamanaVenkata: Thanks. I am very sorry, I just realized there is a typo in my question. The $i$'s in $g(x)$ shouldn't be there. I have edited it. Um, I was expecting something between 0 and 1 (though I might be wrong...) Sorry again. – craig Oct 22 '11 at 9:49

The first condition, that $f'(0)/f'0)=g'(0)/g(0)$, is equivalent to $A=-z/w$ where $z$ and $w$ are the complex number $z=B-C-\mathrm i(B+C)$ and $w=B-C+\mathrm i(B+C)$. If $B$ and $C$ are real numbers, $w=\bar z$ hence $|A|=1$. (The only case when $w=0$ is $B=C=0$, and then $g(0)=0$ hence $g'(0)/g(0)$ does not exist.) The second condition is irrelevant since it uses values at $a$.

share|cite|improve this answer

From the first condition we can conclude :

$(A=-1 \lor k=0 \lor B=C) \land (A=1 \lor k=0 \lor B=-C)$

From the second condition we have that:

$(k=0 \lor C=Be^{2ka}) \land (k=0 \lor C=-Be^{2ka})$


$a)$if $k=0 \Rightarrow A$ is undetermined

$b)$if $B=\pm C=0 \Rightarrow A$ is undetermined

If we observe the second condition we can see that $C$ cannot be at same time $Be^{2ka}$ and $-Be^{2ka}$ which means that $k=0 \lor B=\pm C=0$,therefore $A$ is undetermined.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.